+) Với mỗi \({x_0} \in \left( { - \infty ;2} \right)\) có \(\mathop {\lim }\limits_{x \to {x_0}} f\left( x \right) = \mathop {\lim }\limits_{x \to {x_0}} \left( {x - 1} \right) = {x_0} - 1 = f\left( {{x_0}} \right)\)
Do đó hàm số \(f\left( x \right)\) liên tục tại \({x_0} \in \left( { - \infty ;2} \right).\)
+) Với mỗi \({x_0} \in \left( {2; + \infty } \right)\) có \(\mathop {\lim }\limits_{x \to {x_0}} f\left( x \right) = \mathop {\lim }\limits_{x \to {x_0}} \left( { - x} \right) = - {x_0} = f\left( {{x_0}} \right)\)
Do đó hàm số \(f\left( x \right)\) liên tục tại \({x_0} \in \left( {2; + \infty } \right).\)
+) Với mỗi \({x_0} = 2\) có \(\mathop {\lim }\limits_{x \to {2^ - }} f\left( x \right) = \mathop {\lim }\limits_{x \to {2^ - }} \left( {x - 1} \right) = 2 - 1 = 1;\mathop {\lim }\limits_{x \to {2^ + }} f\left( x \right) = \mathop {\lim }\limits_{x \to {2^ + }} \left( { - x} \right) = - 2\)
\( \Rightarrow \mathop {\lim }\limits_{x \to {2^ - }} f\left( x \right) \ne \mathop {\lim }\limits_{x \to {2^ + }} f\left( x \right)\) do đó không tồn tại \(\mathop {\lim }\limits_{x \to 2} f\left( x \right).\)
Vậy hàm số \(f\left( x \right)\) gián đoạn tại \({x_0} = 2\) nên hàm số \(f\left( x \right)\) không liên tục trên \(\mathbb{R}.\)